2021
DOI: 10.1002/ddr.21815
|View full text |Cite
|
Sign up to set email alerts
|

Potential antiviral activity of isorhamnetin against SARS‐CoV‐2 spike pseudotyped virus in vitro

Abstract: Coronavirus Disease 2019 (COVID-19) cases and deaths are still rising worldwide, there is currently no effective treatment for severe inflammation and acute lung injury caused by new coronavirus (SARS-COV-2) infection. Therapies to prevent or treat COVID-19, including antiviral drug and several vaccines, are still being development. Human angiotensin-converting enzyme 2 (ACE2), expressing in lung, has been confirmed to be a receptor for SARS-COV-2 infection, interventions for attachment of spike protein of SAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 45 publications
0
49
0
Order By: Relevance
“…Chemophenetically isorhamnetin glycosides prevail over quercetin glycosides [ 19 ]. Recent findings on the isorhamnetin’s capability to bind to human angiotensin-converting enzyme 2 and prevent the SARS-CoV-2 virus from entering the cells [ 13 ] could initiate further research on the valorization of HR leaves for the production of isorhamnetin. The leaf powders of ‘Otradnaja’ and ‘Podarok Sadu’ were determined with the greatest amounts of kaempferol derivatives.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Chemophenetically isorhamnetin glycosides prevail over quercetin glycosides [ 19 ]. Recent findings on the isorhamnetin’s capability to bind to human angiotensin-converting enzyme 2 and prevent the SARS-CoV-2 virus from entering the cells [ 13 ] could initiate further research on the valorization of HR leaves for the production of isorhamnetin. The leaf powders of ‘Otradnaja’ and ‘Podarok Sadu’ were determined with the greatest amounts of kaempferol derivatives.…”
Section: Resultsmentioning
confidence: 99%
“…The traditional medicinal systems incorporate the fruits and leaves of HR in the treatment of various ailments of digestive, hepatic, and cardiovascular systems, as well as skin diseases [ 3 , 4 ]. In vitro and in vivo studies have confirmed the anti-inflammatory, antitumor, hepatoprotective, immunomodulatory, anti-atherogenic, anti-stress, hepatoprotective, radioprotective, tissue repair, antibacterial, antifungal, antiviral, and antioxidant activities, which are determined by the multichemical origin compounds [ 4 , 9 , 10 , 11 , 12 , 13 ]. Fruits and leaves contain rich profiles of carotenoids, tocopherols, amino acids, triterpenic compounds, and phenolic compounds [ 3 , 5 , 7 , 8 , 10 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liu et al (2021) found that baicalein could inhibit SARS-CoV-2 3CLpro activity in vitro with IC50 values of 8.52 µg/ml and 0.39 µM. The effect of isorhamnetin binding to ACE2 was demonstrated by the surface plasmon resonance assay, and it was shown by in vitro virus experiments that isorhamnetin could inhibit SARS-CoV-2 spike pseudotyped virus entering ACE2h cells (Zhan et al, 2021). Antiinflammatory and antiviral effects of stigmasterol and β-sitosterol were demonstrated in in vitro experimental studies (Petrera et al, 2014;Liao et al, 2018).…”
Section: Common Pharmacological Actions and Mechanismsmentioning
confidence: 99%
“…Lindl., and Ginkgo biloba L., and isorhamnetin found in Lepidium apetalum Willd., Eriobotrya japonica (Thunb.) Lindl., Ginkgo biloba L., and Aster tataricus L.f. exhibit the ability to prevent SARS-CoV-2 from entering into ACE2 + cells (Henss et al, 2021;Maiti and Banerjee, 2021;Zhan et al, 2021). Neochlorogenic acid from Tussilago farfara L. and Lianhuaqingwen granules inhibit the ACE2 enzyme activity (Chen et al, 2021a).…”
Section: Viral and Bacterial Infectionsmentioning
confidence: 99%